Contribution of precipitation and temperature to multiscale drought variations over Asia: Dependence on the time scale. (5th July 2022) - Zhang, Jianmin; Wu, Renguang; Jia, Xiaojing; Zhang, Yanting
Abstract: Drought variations are determined by precipitation and temperature changes. The present study examines the relative contributions of precipitation and temperature to temporal variations of short‐term, medium‐term and long‐term droughts over Asia. This is accomplished by comparing (a) the variations of Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) that extend over 3, 9 and 24 months (i.e., short‐term, medium‐term and long‐term droughts, respectively) and (b) the strength of the relationship of SPEI to precipitation and temperature. Both precipitation and temperature contribute to variations of the north–south dipole pattern of short‐term and medium‐term droughts with a relatively larger contribution from temperature. The contribution of precipitation and temperature to the variations of long‐term drought depends upon the spatial pattern. The variation of the north–south dipole pattern of long‐term drought is mainly contributed by the temperature trend with additional contribution of precipitation in eastern and southwestern Asia. The variation of the southwest–northeast tripole pattern of long‐term drought is mainly contributed by precipitation in central Asia and has a comparable contribution of precipitation and temperature in southern and eastern Asia. The tripole pattern and dipole pattern of long‐term drought have a closer relation to the Pacific Decadal Oscillation (PDO) and Atlantic Multidecadal Oscillation (AMO), respectively. The PDO effect on long‐term drought variation is mainly through modulating precipitation. Abstract : Both precipitation and temperature contribute to the north–south dipole pattern variation of short‐term and medium‐term droughts with a relatively larger contribution from temperature. The north–south dipole pattern variation of long‐term drought is mainly contributed by the temperature trend with a supplementary contribution of precipitation in eastern and southwestern Asia. The southwest–northeast tripole pattern variation of long‐term drought is mainly contributed by precipitation in central Asia and has a comparable contribution from precipitation and temperature in southern and eastern Asia.